Mechanism of a Bad Bank is to Reduce Stress Assets for achieving economic growth and Financial Stability - K.M, Mahesh; Aithal, P.S. (Gyan Management Journal, 2021)
The setting of Bad bank for purpose of resolve the Non-Performing Assets/ Taxie Assets.1US based Mellon Bank created the First bad back in 1988. Government created2Stressed Asset Stabilization Fund (SASF) in 2004, When IDBI was converted in to Bank. The 2008 Financial Crises, Coronavirus Pandemic 19 ,implementation of 3Bankruptcy Code and the recent amendment to the Banking Regulation Act4,creation of a ‘bad bank mechanism is assess the bad loans of corporate, individuals , Small and Medium enterprise’s(SME), PMMY and the true extent of stressed assets. Bad Bank mechanism has been implemented in other countries including Sweden, Finland, France and Germany5, Japan set up bad bank in the name of Credit Co-operative Purchasing Company which bought the stressed